ANALISIS GAMBAR DIGITAL UNTUK SERANGAN PENYAKIT LAYU FUSARIUM DI PISANG MENGGUNAKAN IMAGEJ - Ahmad Zaelani; Wulan S. Kurniajati; Herlina Herlina; Diyah Martanti; Fajarudin Ahmad (BERITA BIOLOGI, 2020)
Fusarium wilt disease caused by Fusarium oxysporum f. sp. cubense is the most dangerous disease in banana. Recently, development of new banana varieties has been the most effective ways to prevent this disease. To develop the resistant banana, Fusarium severity analysis is the important part in the process of Fusarium disease assessment to quantify the disease severity.. The objective of this study was to develop digital image analysis method for Fusarium severity analysis by using software ImageJ. Pisang Ambon and Pisang Cavendish were used as plant material due to its susceptibility of the disease. Fusarium severity analysis performed as follows (i) Photographing of Fusarium-infected rhizom (ii) Digital image analysis by using ImageJ of the taken image. The analysis result was percentage area of Fusarium-infected rhizom, represented by necrosis and discoloration. The percentage of rhizome infected by Fusarium- of Pisang Ambon#1 was 50.10%, while Pisang Ambon#2 was 22.23%. In addition, the percentage of Pisang Cavendish#1 and Pisang Cavendish#2 was 28.52% and 39.5%, respectively. Digital image analysis of the sample showed consistent result and more objective. Development of the digital image analysis is not only useful for Fusarium severity analysis in Banana, but also for other crops.